Role of Head Teacher in School Management: A Case of High School in China - Pant, Sambid Bilas (Education and Development, 2020)
Head teachers (HTs) have a crucial role in school leadership as well as in education policy agendas internationally. School leadership plays a key role in improving school outcomes as well as the school environment by motivating teachers. This study was carried out considering the major roles of the HT in making school programmes effective in Chinese context. Data were collected through interviews with students and teachers; review of books, reports, journals, and various publications with a view to explore the role of HT. The school website (in Chinese language translated to English) was also studied for information. The study revealed that HT is the most senior teacher and leader of a school, responsible for the education of all pupils, management of staff, and for school policy making. There is a positive moderate relationship between the leadership style and students’ academic performance in high school. This study has also established that the leadership that is instrumental towards school improvement is of ‘distributed’ kind of leadership; and the coordinated and collaborative efforts of the HT, teachers, students, parents, community leaders, district administrator and others becomes instrumental in ensuring the quality of education in school.